Hadith #4605 - Sunan Abi Dawud - Abdur Rahman bin 'Amr bin 'Absa عبد الرحمن بن عمرو بن عبسة; Ahmad bin Hanbal أحمد بن حنبل; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Khalid bin Ma'dan خالد بن معدان; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Abi Dawud)
The Prophet (ﷺ) said: Let me not find one of you reclining on his couch when he hears something regarding me which I have commanded or forbidden and saying: We do not know. What we found in Allah’s Book we have followed.
Grade: Sahih